Corona virus diseases (Covid-19): Sebuah tinjauan literatur - Yuliana, Y (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Coronavirus Disease (Covid-19). In 2020, a new type of coronavirus (SARS-CoV-2) was spread, called a disease called Coronavirus disease 2019 (COVID-19). This virus was discovered in Wuhan, China for the first time and has infected 90,308 people as of March 2, 2020. The number of deaths reached 3,087 people or 6%, the number of patients recovering 45,726 people. This type of single positive RNA strain infects the human respiratory tract and is sensitive to heat and can effectively be activated by chlorine-containing disinfectants. The source of the host is thought to come from animals, especially bats, and other vectors such as bamboo rats, camels and ferrets. Common symptoms include fever, cough and difficulty breathing. Clinical syndrome is divided into uncomplicated, mild pneumonia and severe pneumonia. Specimen examination is taken from the throat swab (nasopharynx and oropharynx) and lower airway (sputum, bronchial rinse, endotracheal aspirate). Isolation was carried out on patients proven to be infected with Covid-19 to prevent wider spread. Abstrak: Penyakit Virus Corona (Covid-19) tahun 2020 merebak virus baru coronavirus jenis baru (SARS-CoV-2) yang penyakitnya disebut Coronavirus disease 2019 (COVID-19). Virus ini ditemukan di Wuhan, China pertama kali dan sudah menginfeksi 90.308 orang per tanggal 2 Maret 2020. Jumlah kematian mencapai 3.087 orang atau 6%, jumlah pasien yang sembuh 45.726 orang. Virus jenis RNA strain tunggal positif ini menginfeksi saluran pernapasan manusia dan bersifat sensitif terhadap panas dan secara efektif dapat diinaktifkan oleh desinfektan mengandung klorin. Sumber host diduga berasal dari hewan terutama kelelawar, dan vektor lain seperti tikus bambu, unta dan musang. Gejala umum berupa demam, batuk dan sulit bernapas. Sindrom klinik terbagi menjadi tanpa komplikasi, pneumonia ringan dan pneumonia berat. Pemeriksaan spesimen diambil dari swab tenggorok (nasofaring dan orofaring) dan saluran napas bawah (sputum, bilasan bronkus, aspirat endotrakeal). Isolasi dilakukan pada pasien terbukti terinfeksi Covid-19 untuk mencegah penyebaran lebih luas.